Lactobacillus rhamnosus and Lactobacillus delbrueckii ameliorate the expression of miR-155 and miR-181a in SLE patients. (September 2018) - Vahidi, Zohreh; Samadi, Morteza; Mahmoudi, Mahmoud; RezaieYazdi, Zahra; Sahebari, Maryam; Tabasi, Nafiseh; Esmaeili, Seyed-Alireza; Sahebkar, Amirhossein; Rastin, Maryam
Graphical abstract: Highlights: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease. miR-155 and miR-181a are associated with the severity of SLE. Probiotics are known to possess immunomodulatory and anti-inflammatory effects. Treatment of PBMCs with probiotic strains decreased miR-155 and miR-181a expression. L. rhamnosus and L. delbrueckii might be beneficial in the management of SLE patients. Abstract: Background: Systemic lupus erythematosus (SLE) is a chronic inflammatory autoimmune disease characterized by the production of autoantibodies and activated immune cells against self-antigens. Probiotics are known to possess anti-inflammatory and modulatory effects on the immune responses. In this study, we evaluated the effect of probiotics Lactobacillus rhamnosus and Lactobacillus delbrueckii on the expression levels of miR-155 and miR-181a in the PBMCs of SLE patients. Methods: A total of 20 newly diagnosed SLE patients and 20 healthy controls were enrolled in this study. Peripheral blood mononuclear cells (PBMCs) were isolated from whole blood and treated with probiotics Lactobacillus rhamnosus (10 7 Bac/mL) and Lactobacillus delbrueckii (10 5 Bac/mL), and cultured in RPMI-1640 for 48 h. Afterwards, total RNA containing micro-RNAs were extracted. cDNA was synthesized for miRNAs and gene expression of miR-181a and miR-155 was analyzed using quantitative real-time PCR method. Results: Higher expression levels of miR-181a and miR-155 were found in SLE patients compared with healthy controls. Treatment of PBMCs with L. rhamnosus, L. delbrueckii and combination of these probiotics downregulated the expression of miR-181a and miR-155 in treated cells compared with untreated cells. Conclusions: L. rhamnosus and L. delbrueckii modulate the expression of miR-181a and miR-155 in SLE patients and might be beneficial in the management of SLE patients.